Pickering Emulsions Using Pd NP-loaded pH-sensitive Carboxylated Cellulose Nanocrystals for Catalytic Hydrogenation - Dandan Li; Feichao Miao; Jinhua Chen; Zhibing Liu; Zhiyuan Wang; Yang Wang (BioResources)
Exploiting stimuli-responsive Pickering interfacial catalysts is crucial to the development of organic reactions in water and green chemistry. Herein, amphiphilic carboxylated cellulose nanocrystals were synthesized by surface modification of hydrophilic carboxylated cellulose nanocrystals. The obtained amphiphilic carboxylated cellulose nanocrystals showed great toluene-in-water Pickering emulsion stabilization capacity and pH-responsive property. Emulsification and rapid demulsification behaviours were observed by simple pH adjustment. Palladium nanoparticles supported on the amphiphilic carboxylated cellulose nanocrystals exhibited high activity in the hydrogenation reaction of nitrobenzene in aqueous media because of the improved mass transfer between hydrophobic substrate and hydrophilic solvent. Moreover, the pH-responsiveness of amphiphilic carboxylated cellulose nanocrystals could promote the recovery of both products and the Pickering interfacial catalyst. Therefore, palladium nanoparticles loaded bio-derived carboxylated cellulose nanocrystals for efficient pH-switched Pickering emulsion catalytic hydrogenation was successfully prepared. Outstanding activity and reusability were achieved.